On mushrooms and music museums - Losleben, Katrin (Septentrio Conference Series, 2019)
This paper examines a feminist approach to curating music history and historiography. By exhibiting instruments, pictures, sounds, memorabilia of mostly composers, sometimes instrumentalists or instrument builders, music museums process narratives about music and its history to their visitors. Music history however is, as generations of feminist musicologists have pointed out, strongly shaped by the neglect of perspectives of female and non-heterosexual experiences. Historiography gravitates to and from male actors and taxonomies (Losleben 2017). As Meaghan Morris pointed out, feminism “is not easily adapted to heroic progress narratives”, in which these narratives are rooted and continue to contribute to; neither do feminist ideals and patriarchal structures in which museums are embedded go together well. My aim is to uncover from a feminist point of view these relations in which curating in ´ music instrument museums´ and popular music museums are embedded and how a feminist approach might be possible even so.